Maintenance practice works in Hospital Universiti Sains Malaysia (HUSM) Kubang Kerian, Kelantan / Nurul Izzati Mohd Sukri - Mohd Sukri, Nurul Izzati (2014)
The building maintenance can be defined as the regular inspection of all part of the building and the execution of work necessary to keep the structure, finishes and fitting in a proper and acceptable state of repair, including decoration both internally and externally (Cripps, 1984). The British Standard 8210 defined maintenance as the combination of all technical and administrative action intended to retain an item in, or restore it to a state in which it can perform its required function. In HUSM, the maintenances of UKP always emphasize on the building condition that are always in good condition and safe to use in a long time.